CISSP PASSPORT - Rogers, Bobby E. (MCGRAW-HILL EDUCATION, 2022)
This quick review study guide offers 100% coverage of every topic on the latest version of the CISSP exam Get on the fast track to becoming CISSP certified with this affordable, portable study tool. Inside, cybersecurity instructor Bobby Rogers guides you on your career path, providing expert tips and sound advice along the way. With an intensive focus only on what you need to know to pass (ISC)2®'s 2021 Certified Information Systems Security Professional exam, this certification passport is your ticket to success on exam day. Designed for focus on key topics and exam success: List of official exam objectives covered by domain Exam Tips offer expert pointers for success on the test Cautions highlight common pitfalls and real-world issues as well as provide warnings about the exam Tables, bulleted lists, and figures throughout focus on quick reference and review Cross-Reference elements point to an essential, related concept covered elsewhere in the book Additional Resources direct you to sources recommended for further learning Practice questions and content review after each objective section prepare you for exam mastery Covers all exam topics, including: Security and Risk Management Asset Security Security Architecture and Engineering Communication and Network Security Identity and Access Management (IAM) Security Assessment and Testing Security Operations Software Development Security Online content includes: Customizable practice exam test engine 300 realistic practice questions with in-depth explanations.